Karakteristik Korporat Dan Corporate Social Responsibility Pada Perusahaan Media Yang Terdaftar Di Bursa Efek Indonesia - Cindy, Cindy; Damayanti, Wan Mediasari; Mardiah, Ainun (Jurnal Ilmiah Wahana Pendidikan, 2023)
The balance of the relationship between companies and society can be managed through Corporate Social Responsibility (CSR). This is essential for the smooth operation of a company. CSR helps companies reduce the social and environmental consequences. This study aims to uncover how different variables influence CSR policies in media companies that have met the requirements to be listed on the Indonesia Stock Exchange (BEI) between 2017 and 2022. The observed variables include company size, liquidity ratios, solvency ratios, activity ratios, and profitability ratios. A total of 9 companies were selected as the research sample through purposive sampling method. The researcher used multiple linear regression analysis. The findings indicate that company size, liquidity ratio using Current Ratio (CR), and solvency ratio using Debt To Asset Ratio (DAR) do not have an impact on corporate CSR disclosure. However, activity ratio using the Total Asset Turnover (TATO) indicator and profitability ratio using the Return on Asset (ROA) indicator significantly influence corporate CSR disclosure.